Community Service: Food Safety Management Education and Practice Among Food Handlers in a Tourism Destination Area - Sri Peni Wastutiningsih; Lily Arsanti Lestari; Sri Nuryani Hidayah Utami; Partini Partini; Niken Meilani Meilani (Poltekkes Kemenkes Surakarta, 2026)
Background: Food safety is a critical issue in the tourism sector, as handling unsafe food can lead to foodborne diseases and negatively affect public health and tourist satisfaction. Food handlers play an important role in maintaining food safety; however, their knowledge and practice are often still inadequate. This community service activity aimed to improve the knowledge of food handlers regarding food safety management at Negeri Kahyangan Tourism. Methods: This activity was conducted on November 21, 2025, in Negeri Kahyangan Torism, Wonolelo Village, Sawangan District, Magelang Regency, involving 24 food handlers. This community service included educational sessions and hands-on practice on food safety management, covering personal hygiene, cross-contamination prevention, temperature control, and proper food handling. Evaluation was conducted using pretest and posttest questionnaires consisting of 15 items. Data were analyzed using the Wilcoxon test. Results: The results showed an increase in the average knowledge score from 67.5 (pretest) to 79.72 (post test). The proportion of participants with good knowledge increased from 25% to 54.2%, while those with poor knowledge decreased from 20.6% to 0%. Statistical analysis indicated a significant improvement (p=0.002). However, some misconceptions remained, particularly regarding food handling during illness (66.7% incorrect), waste management (41.7%), and microbial contamination (37.5%). Conclusion: The community service program was effective in improving food handlers’ knowledge of food safety management. However, continuous education and practical reinforcement are needed, especially on critical aspects such as personal hygiene, waste management, and contamination prevention, to ensure safer food handling practices in tourism settings.